Peculiarities of the mutually caused development of personality self-consciousness and Self-concept - Lypka, Mariana (Psyhology & society, 2019)
The article highlights peculiarities of the holistic development of self-consciousness, Self-concept and self-esteem as a dialectical complementary of general, special and individual categories in the core of a personality psycho-spiritual life. At the same time, self-consciousness is considered as a holistic psychic new formation, which arises ontogenetically later than consciousness, and the essence of which lies in self-awareness. The dynamic center of consciousness is the Self, which controls the behavior, communication and actions of a human, and the central formation of self-consciousness is the Self-concept that constitutes a system of representations (Self-image), attitudes (Self-attitude), actions (Self-deed) an interconnected set of personality installations that are directed towards himself. It is proved that self-esteem represents a “cell” of self-consciousness, essentially reflects the value and significance that a person attributes to himself. It was made a constructive analysis of the three stages of the self-consciousness development, which was singled out by the German philosopher G. W. F. Hegel: a single, special and general dimension of self-consciousness. It is established that at the personal level, self-consciousness in the structural ratio is a unity of four sides which are caused by a human actions: cognitive (the self-cognition), emotional-valuable (the self-attitude), psycho-regulative (the self-regulation), reflexive (the self-awareness).